APLIKASI ADMINISTRASI KEUANGAN PONDOK PESANTREN ADDAINURIYAH 2 BERBASIS WEB MOBILE - Ali Basri, Muhamad; Alfa Razaq, Jeffri (Information Technology and Telematics, 2018)
ABSTRACT Pondok Pesantren Addainuriyah 2 was established in 1980, from the time of its establishment until Currently the income of the financial data that takes place at the addainuriyah 2 pesantren is done manually by the Financial treasurer. financial management is done by manual writing on the book course. Data collection method used is the method of observation, interview and literature study. Methodology of system development in this research use Waterfall methodology. The results in this study are the creation financial management applications Pondok Pesantren Addainuriyah 2 berbasis web mobile,and in the management of research using the method First In First Out for this system aims to facilitate the arrangement in financial management in boarding school addainuriyah 2.